Do referrals improve the representation of women in mobile phone surveys? - Glazerman, Steven; Grépin, Karen A.; Mueller, Valerie; Rosenbaum, Michael; Wu, Nicole (Elsevier, 2023)
Random digit dial surveys with mobile phones risk under-representation of women. To address this, we compare the characteristics of women recruited directly with those of women recruited through referrals from male household members. The referral process improves representation of vulnerable groups, such as young women, the asset poor, and those living in areas with low connectivity. Among mobile phone users, we show a referral (rather than a direct dial) protocol includes more nationally representative proportions of women with these attributes. While seeking intra-household referrals may improve representation, we show that it does so at a higher cost.